Single Nucleotide Polymorphisms in Plasmodium falciparum Genes: Their Roles in Antimalarial Drugs Resistance and Recent Detection Strategies - Zahra, Raihanny Andrea; Fanshur, Ananda Maulana; Saraswati, Aurelia Maria Prajna; Rahmani, Nurul Inayah (Indonesian Journal of Medical Chemistry and Bioinformatics, 2023)
Introduction: Malaria is a serious tropical disease with Plasmodium falciparum as its most well-known causative parasite for producing higher levels of late stage parasites that leads to sequestration in vital organs which could lead to death. There is a growing trend of antimalarial drugs resistance against Plasmodium falciparum. Molecular assessment using polymerase chain reaction could trace the presence of mutation and also determine single-nucleotide polymorphism (SNP) in Plasmodium falciparum genes. This SNP can determine the particular population’s response to antimalarial drugs. Objectives: This study aims to examine the relationship between SNP in Plasmodium falciparum genes and antimalarial drugs resistance. Methods: Literature searches were carried out through various databases which were then collected and analyzed. Result: We identified various SNPs from eleven known genes in Plasmodium falciparum, each SNPs causes a different mechanism which contributes to antimalarial drug resistance. Mechanisms varying from slower drug clearance to drug transport activity alteration. Conclusion: Results from most studies included in this review suggest that SNPs in Plasmodium falciparum genes participate in the resistance against various antimalarial drugs via several mechanisms and may be necessary for parasite survival when stressed.